Practical formal synthesis of D-(+)-biotin from 4-formylazetidin-2-one - Kale, Ajaykumar S.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
A practical synthesis of (3S,6R)-1,3-dibenzyltetrahydro-1H-furo[3,4-d]imidazole-2,4-dione, an important intermediate in the synthesis of biotin, from 4-formyl-3-mesyloxyazetidin-2-one has been achieved. Acid-catalyzed azetidin-2-one ring opening followed by a one-pot conversion of diamine hydrochloride to a cyclic urea and hydroxymethylene to chloromethylene by triphosgene to obtain (4S,5R)-methyl-1,3-dibenzyl-5-chloromethyl-2-oxoimidazolidine-4-carboxyl ate is the key step in this synthesis.
Keywords: azetidin-2-one; beta-Lactams; cyclization; Lactone; reduction

Efficient formal synthesis of (S)-dapoxetine from enantiopure 3-hydroxy azetidin-2-one - Chincholkar, Pinak M.; Kale, Ajaykumar S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2009)
An efficient formal synthesis of S-(+) dapoxetine starting from 3-hydroxy azetidin-2-one is described. The intermediate (S)-3-(dimethyl amino)-3-phenylpropan-1-ol was synthesized in enantiopure form starting with 3-hydroxy azetidin-2-one in seven steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Azetidin 2 ones; beta-Lactams; Enantioselective synthesis; reduction; Staudinger reaction

First iodocyclization reaction of allene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Jadhav, Amol R.; Lahore, Santosh V.; Kahar, Nilesh M.; Joshi, Rohini R.; Joshi, Ramesh A.; Koketsu, Mamoru (Tetrahedron Letters, 2014)
The regioselective iodocyclization reaction of allene-thioureas is described, for the first time, for the synthesis of bicyclic beta-lactams. The substitution at the allenyl part heavily influenced the iodocyclization reaction. The iodocyclization reaction of the unsubstituted allene-thioureas afforded six-membered 3-thia-1-dethiacephems whereas, the substituted allene-thiourea afforded seven-membered thiazepines along with five-membered isopenams. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Allene; beta-Lactams; Iodocyclization; Regioselective; thiourea